Synopsis: Women’s empowerment in agriculture and dietary diversity in Ethiopia - Yimer, Feiruz; Tadesse, Fanaye (International Food Policy Research Institute, 2016)
Using household survey data from 2013 covering more than 7,000 households in five regions of Ethiopia, we investigate the impact of women’s empowerment in agriculture on the nutritional outcomes of children and women. We use multivariate regression methods and instrumental variable techniques to establish the relationship between women’s empowerment and the dietary diversity of women and children. The results show that the indicators for assessing women’s empowerment are all positively related to better dietary diversity for both children and women. As women’s empowerment leads to improvements in children’s and women’s dietary diversity, it follows that interventions which increase women’s empowerment contribute to improving child nutrition as well as their own well-being.